From typhoons to traders: the role of patron-client relations in mediating fishery responses to natural disasters. (16th April 2019) - Drury O'Neill, Elizabeth; Crona, Beatrice; Ferrer, Alice Joan G; Pomeroy, Robert
Abstract: The majority of the world's fishers, fishworkers and their dependents live in coastal tropical areas that are, and will be, highly exposed to human-induced climate change. Projections indicate such change could result in coastal populations being more frequently and acutely impacted by natural disasters. Increasing aid interventions is a likely knock-on effect of such scenarios. How these external natural and social disturbances interact and affect local fisheries and small-scale producers is in part determined by the internal dynamics of the social-ecological system (SES). Economic vulnerability often characterizes communities in these settings and influences the means with which they navigate changes. The patron-client system is prolific in many rural economies and small-scale fisheries. It forms a central element in the organization of market interactions and often provides much needed finance for low-income households in place of formal options. How such injection of capital promotes individuals' ability to buffer income fluctuations at the expense of long-term sustainability of the broader fishery system is still an area in need of examination. This paper contributes to shed light on this issue by using a case study approach to trace the historical development of the fishery system in the Iloilo Province (Philippines) in relation to a major natural disaster—super-typhoon Haiyan, known locally as Yolanda—and the subsequent aid intervention that followed. The aim is to assess how the patron-client system filtered these two related disturbances and to highlight the resulting tensions between short-term individual resilience and longer-term SES sustainability.